(untitled) (Research, Society and Development, 2021)
The objective of the present study was to evaluate and describe the level of knowledge of Physical Education professionals about the recommendations for prescribing physical exercises for hypertensive individuals in weight training gyms in the east and west of the city of Natal / RN. This is an observational, quantitative, descriptive cross-sectional research. 46 professionals were interviewed, 41 men 31.0 (± 7.2) years old and 5 women 31.2 (± 5.1) years old. Participated in this study professionals who worked in gyms in the east and west of Natal / RN with at least 5.8 (± 6.6) years of experience. For data analysis, the mean was used, as well as the percentage of responses. Professionals duly registered with CREF16 / RN were included in the study. The study showed results where 91.3% worked with hypertensive patients and that 61.5% knew only one criterion for measuring blood pressure according to the VII Brazilian Guideline for Hypertension. Still, only 56.5% knew the criteria for hypertensive patients not to start exercising that day and about medicines only 54.3% informed the name of at least 1 of these drugs in hypertension. It is concluded, therefore, that the knowledge of these professionals for this audience was still insufficient according to the recommendations of the VII Brazilian Guideline on Hypertension and science on training for special groups with cardiovascular risk. It is suggested that more studies be carried out to obtain data to assist in the elaboration of programs aimed at professional performance, facing students with arterial hypertension.